2023
DOI: 10.4088/jcp.23f15099
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Health, 1

Chittaranjan Andrade

Abstract: Clinical and Practical Psychopharmacology Read the ColumnEach month in his online column, Dr Andrade considers theoretical and practical ideas in clinical psychopharmacology with a view to update the knowledge and skills of medical practitioners who treat patients with psychiatric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…As is immediately apparent, these behaviors are common in everyday life; consequently, the average person is sedentary for 9-10 h/d. 1 Many studies have shown that, independent of engagement in health-related physical activity, greater sedentary time is associated with higher risks of adverse physical and mental health outcomes. The previous article in this column presented an overview on sedentariness and its possible effects on physical and mental health.…”
Section: J Clin Psychiatry 2024;85(1):24f15270mentioning
confidence: 99%
See 1 more Smart Citation
“…As is immediately apparent, these behaviors are common in everyday life; consequently, the average person is sedentary for 9-10 h/d. 1 Many studies have shown that, independent of engagement in health-related physical activity, greater sedentary time is associated with higher risks of adverse physical and mental health outcomes. The previous article in this column presented an overview on sedentariness and its possible effects on physical and mental health.…”
Section: J Clin Psychiatry 2024;85(1):24f15270mentioning
confidence: 99%
“…The previous article in this column presented an overview on sedentariness and its possible effects on physical and mental health. 1 This article specifically examines associations between sedentariness and dementia as demonstrated in a recently published cohort study. 2…”
Section: J Clin Psychiatry 2024;85(1):24f15270mentioning
confidence: 99%